THE INSEPARABLE NARRATOLOGY AND GENRE IN DISNEY’S ALADDIN (2019): A STRUCTURALIST CRITICISM - Sandi Hamim (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2020)
The current study aims to analyze the narratology and to identify the genre of Disney’s Aladdin (2019). It also discusses the relationship between narratology and the genre in the movie. The theories used in this study are narratology theory by Vladimir Propp and genre analysis by Northrop Frye with the structuralist criticism perspective. The study used the descriptive qualitative method. The findings of this study provide pieces of evidence that Disney’s Aladdin movie can be analyzed using Propp’s narratology. There are 30 of 31 functions of dramatis personae and 7 of 7 dramatis personae found in the movie. Those findings are deducted by focusing on the plot and characters in the movie. According to those findings, the genre of the movie based on Frye’s theory of myths is the mythos of spring (comedy). This is because the movie moves from the mythos of winter to summer (irony to romance). This finding is supported by the existence of the elements of conflict, disorder and confusion, and the triumph of traditional quest theory. It also supported by the existence of the category of irony, romance, and comedy (theory of modes in the movie. Hence, the researcher deduces that the narratological analysis and the genre in this study are intercorrelated and support one another.